Black Phosphorus Tagged Responsive Strontium Hydrogel Particles for Bone Defect Repair - Zhengwei Liu; Hui Zhang; Jingjing Gan; Yuanjin Zhao; Yongxiang Wang (Advanced Science)
Abstract Hydrogel‐derived implants have proven value in bone tissue regeneration, and current efforts have concentrated on devising strategies for producing functional implants with desired structures and functions to improve therapeutic outcomes. Herein, a novel black phosphorus (BP) tagged responsive strontium (Sr) hydrogel particles are presented for bone defect repair. By applying microfluidic technology, Sr and carboxymethyl chitosan, and BP are integrated into poly(N‐isopropyl acrylamide) (pNIPAM) hydrogel matrix to generate such microparticles called pNBCSMs. Upon exposure to near‐infrared irradiation, the pNBCSMs experience volume shrinkage and provoke the extrusion of the incorporated Sr, ascribed to the photothermal conversion ability of BP and the thermosensitivity of pNIPAM. In vitro and in vivo experimental results reveal that pNBCSMs subjected to near‐infrared light display superior anti‐inflammatory, anti‐apoptotic, bacterial inhibitory, as well as osteogenesis‐promoting effects, thereby effectively improving defective cranial bone repair. These features suggest that the proposed pNBCSMs can be promising candidates for bone repair.